2022
DOI: 10.1038/s41598-022-06483-2
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence in positioning between mandibular third molar and inferior alveolar nerve on panoramic radiography

Abstract: Determining the exact positional relationship between mandibular third molar (M3) and inferior alveolar nerve (IAN) is important for surgical extractions. Panoramic radiography is the most common dental imaging test. The purposes of this study were to develop an artificial intelligence (AI) model to determine two positional relationships (true contact and bucco-lingual position) between M3 and IAN when they were overlapped in panoramic radiographs and compare its performance with that of oral and maxillofacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…reported a classi cation accuracy of 0.723. [29] The accuracy of the deep learning model in this study was 0.766, which is almost the same as the classi cation accuracy. In addition, the diagnostic accuracy of specialists was 0.55 to 0.72 (average 0.63), and it was di cult for even specialists to evaluate the continuity between the inferior alveolar nerve and the mandibular third molar using only panoramic radiographic images.…”
Section: Discussionsupporting
confidence: 59%
“…reported a classi cation accuracy of 0.723. [29] The accuracy of the deep learning model in this study was 0.766, which is almost the same as the classi cation accuracy. In addition, the diagnostic accuracy of specialists was 0.55 to 0.72 (average 0.63), and it was di cult for even specialists to evaluate the continuity between the inferior alveolar nerve and the mandibular third molar using only panoramic radiographic images.…”
Section: Discussionsupporting
confidence: 59%
“…All studies were observational studies except four [ 15 , 16 , 17 , 18 ], which were experimental studies. The types of observational studies included were a mixture of descriptive studies (case report, case series, cross-sectional, qualitative studies) and analytic studies (cohort, case-control).…”
Section: Resultsmentioning
confidence: 99%
“…Analysis using deep learning was performed to determine the 3D positional relationships from panoramic images without using other imaging devices. In continuity analysis, although it is difficult to simply compare performance in deep learning studies conducted on different data, a deep learning classification study conducted on 571 images by Choi et al reported a classification accuracy of 0.723 32 . The accuracy of the deep learning model in this study was 0.766, which is almost the same as the classification accuracy.…”
Section: Discussionmentioning
confidence: 99%